TIME,RHYTHMANDMUSICAL THOUGHT (Orfeu, 2020)
Composers from the beginning of 20th Century found diverse ways to transcendmetrical rhythm. These approaches to the temporal dimensionofmusic would recall rhythmic practices from an era before the consolidation of musical meter and tonal harmony. As one goes throughout these moments of music history, different ways in which time and musical thought were intertwined reveal themselves. Musical excerpts from scores reveal different efforts in order to transcend rhythmic and metric phraseology.
Keywords: duration; meter; rhythm; musical time; Time